A transient rise in agalactosyl IgG correlating with free interleukin 2 receptors, during episodes of erythema nodosum leprosum. - Filley, E (1989)
The proportion of oligosaccharide chains on the Fc fragment of IgG which terminate with N-acetylglucosamine and not galactose (%GO) has previously been shown to be raised in rheumatoid arthritis (RA), Crohn's disease (CD) and tuberculosis (Tb), but to be normal in sarcoidosis (SA), and in both lepromatous and tuberculoid leprosy. However we have now studied %GO in sequential serum samples collected from lepromatous leprosy patients undergoing episodes of erythema nodosum leprosum (ENL). During ENL %GO is transiently raised, and this rise parallels an increase in circulating interleukin 2 receptors (IL-2R). These findings confirm that changes in T cell function occur during ENL. Moreover it appears that %GO rises when there is, simultaneously, T-cell-mediated tissue damage and an acute phase response (RA, CD, Tb, ENL), but not when there is an acute phase response without major T cell involvement, or chronic T cell activity alone (SA, and tuberculoid leprosy). We suggest therefore that %GO is an indicator of a type of T cell activity with broad immunopathological implications.